2021
DOI: 10.3390/ijms22168467
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Novel Human Acellular Dermal Dressing Sterilization for Routine Use in Clinical Practice

Abstract: Gamma rays and electrons with kinetic energy up to 10 MeV are routinely used to sterilize biomaterials. To date, the effects of irradiation upon human acellular dermal matrices (hADMs) remain to be fully elucidated. The optimal irradiation dosage remains a critical parameter affecting the final product structure and, by extension, its therapeutic potential. ADM slides were prepared by various digestion methods. The influence of various doses of radiation sterilization using a high-energy electron beam on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Qing-Qing Qiu et al [13] reported that E-beam irradiation sterilization cuts the collagen matrix of the ADM. Other studies also report that the gamma and E-beam irradiation used for sterilization accelerate the rate of collagen ber degradation and fragmentation in the ADM [14,15]. The increased rate of degradation and fragmentation compromises the tensile strength of the ADM [14,15]. Since most patients who have undergone BCS surgery undergo radiation therapy, it is accepted that some shrinkage of the ADM will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Qing-Qing Qiu et al [13] reported that E-beam irradiation sterilization cuts the collagen matrix of the ADM. Other studies also report that the gamma and E-beam irradiation used for sterilization accelerate the rate of collagen ber degradation and fragmentation in the ADM [14,15]. The increased rate of degradation and fragmentation compromises the tensile strength of the ADM [14,15]. Since most patients who have undergone BCS surgery undergo radiation therapy, it is accepted that some shrinkage of the ADM will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Strong permeability, no residual toxic agents, and ambient processing temperature are advantages of the method. However, physical, chemical, mechanical, and biological changes bring some troubles 66 . EO reacts with sulfhydryl, amino, and carboxyl groups in proteins and nucleic acid molecules within the microorganisms, leading to their inactivation 67 .…”
Section: Discussionmentioning
confidence: 99%
“…However, physical, chemical, mechanical, and biological changes bring some troubles. 66 EO reacts with sulfhydryl, amino, and carboxyl groups in proteins and nucleic acid molecules within the microorganisms, leading to their inactivation. 67 Sterilization with EO gas is also conducted at room temperature.…”
Section: Sterilization Methodsmentioning
confidence: 99%
“…These opinions are shared by doctors and nutritionists also nowadays [4,5]. Generally, the pro-health properties of linseed oil are explained by specific features of their components [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. This report shows that yet another factor, omitted so far, can be significant: supercriticality [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The positive influence of linseed oil is broadly recognized in the fight against obesity, arthritis, and hypertension [9,13]. Focusing on cosmetics-related issues, it can strengthen skin, support redness reductions, repair skin damage (including flaky epidermis), heal skin burns and frostbite, and create smooth and soft skin [5,9,[17][18][19]22]. Linseed is also indicated as a prophylactic anti-cancer agent for breast, colon, and prostate problems [4,17,19,23].…”
Section: Introductionmentioning
confidence: 99%